IMPLEMENTASI MEDIA PEMBELAJARAN WORDWALL PADA MATERI DAUR HIDUP HEWAN DI KELAS IV SDIT PERMATA HATI BATANG - Nurul Ilma Aulia; Bagas Mukti Nasrowi (CV. Denasya Smart Publisher, 2026)
This research aims to describe the implementation of Wordwall learning media in science learning on the animal life cycle material in grade IV of SDIT Permata Hati Batang and to determine student involvement during the learning process. This study used a qualitative research method with a descriptive approach. The data sources in this research were grade IV teachers and students. Data collection techniques were carried out through interviews and observations. Data validity was tested using source triangulation and technique triangulation, while data analysis was conducted through data condensation, data presentation, and conclusion drawing. The results showed that the implementation of Wordwall learning media was able to create a more interactive and enjoyable learning atmosphere. Students appeared more active, enthusiastic, and involved during the learning process because the media was presented in the form of educational games. The use of Wordwall also helped students understand the animal life cycle material more easily through visual displays and interactive activities. However, several obstacles were still found, such as differences in students’ abilities and limited learning time, causing some students to require additional guidance from the teacher. Despite these obstacles, overall, Wordwall learning media is an effective alternative for improving student engagement and understanding in elementary science school.